Post-COVID Condition in Adults and Children Living in the Same Household in Italy: A Prospective Cohort Study Using the ISARIC Global Follow-Up Protocol - Buonsenso, Danilo; Munblit, Daniel; Pazukhina, Ekaterina; Ricchiuto, Antonia; Sinatti, Dario; Zona, Margherita; De Matteis, Alessia; D’Ilario, Federico; Gentili, Carolina; Lanni, Roberta; Rongai, Teresa; del Balzo, Patrizia; et al. (Frontiers in Pediatrics, 2022)
Background Emeerging evidence shows that both adults and children may develop post-acute sequelae of SARS-CoV-2 infection (PASC). The aim of this study is to characterise and compare long-term post-SARS-CoV-2 infection outcomes in adults and children in a defined region in Italy. Methods A prospective cohort study including children (≤18 years old) with PCR-confirmed SARS-CoV-2 infection and their household members. Participants were assessed via telephone and face-to-face visits up to 12 months post-SARS-CoV-2 diagnosis of household index case, using the ISARIC Covid-19 follow-up survey. Results Of 507 participants from 201 households, 56.4% (286/507) were children, 43.6% (221/507) adults. SARS-CoV-2 positivity was 87% (249/286) in children, and 78% (172/221) in adults. The mean age of PCR positive children was 10.4 (SD 4.5) and of PCR positive adults was 44.5 years (SD 9.5), similar to the PCR negative control groups (children 10.5 years (SD 3.24), adults 42.3 years (SD 9.06)). Median follow-up post-SARS-CoV-2 diagnosis was 77days (IQR 47–169). A significantly higher proportion of adults compared to children reported at least one persistent symptom (67%, 68/101 vs 32%, 57/ 179, p<0.001) at the first follow up. Adults had more frequently coexistence of several symptom categories at both follow-up time-points. Female gender was identified as a risk factor for PASC in adults (p 0.02 at 1-3 months and p 0.01 at 6-9 months follow up), but not in children. We found no significant correlation between adults and children symptoms. In the pediatric group, there was a significant difference in persisting symptoms between those with confirmed SARS-CoV-2 infecton compared to controls at 1-3 months follow up, but not at 6-9 months. Conversely, positive adults had a higher frequency of persisting symptoms at both follow-up assessments. Conclusion Our data highlights that children can experience persistent multisystemic symptoms months after diagnosis of mild acute SARS-CoV-2 infection, although less frequently and less severily than co-habitant adults. There was no correlation between symptoms experienced by adults and children living in the same household. Our data highlights an urgent need for studies to characterise PASC in whole populations and the wider impact on families.